2017
DOI: 10.3354/esr00854
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rearing practice on post-release young-of-the-year behavior: Acipenser sturio early life in freshwater

Abstract: Stocking is becoming an increasingly important conservation tool as biodiversity trends continue to decline. The European sturgeon Acipenser sturio is a Critically Endangered species subject to a stocking program in which a better understanding of its life history and stocking achievement is crucial for its conservation. In this study, acoustic telemetry assessment of postrelease behavior of 3 mo old fish was carried out for the first time on a sturgeon species. We aimed to improve the knowledge of movement, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Fish survival (or proxies thereof) have been monitored in nature after release in a few studies, and results have shown that prerelease exposure to shelter-like structures can increase survival, or at least hint at such effects (Kawabata et al 2011a, D'Anna et al 2012, Hyvärinen and Rodewald 2013, Roberts et al 2014, Carrera-García et al 2017, Mes et al 2019. However, improved postrelease survival is not detected in all studies, including studies on some species where positive behavioral or cognitive effects have been detected (Brockmark et al 2007, Fast et al 2008, Rosengren et al 2017, Solås et al 2019.…”
Section: Social Transfermentioning
confidence: 99%
“…Fish survival (or proxies thereof) have been monitored in nature after release in a few studies, and results have shown that prerelease exposure to shelter-like structures can increase survival, or at least hint at such effects (Kawabata et al 2011a, D'Anna et al 2012, Hyvärinen and Rodewald 2013, Roberts et al 2014, Carrera-García et al 2017, Mes et al 2019. However, improved postrelease survival is not detected in all studies, including studies on some species where positive behavioral or cognitive effects have been detected (Brockmark et al 2007, Fast et al 2008, Rosengren et al 2017, Solås et al 2019.…”
Section: Social Transfermentioning
confidence: 99%
“…Additionally, studies on the performance and behavior of fish stocks have been scarce and more challenging compared to research on their general biological characteristics such as growth, food habits, and reproduction. Previous reports on the post-release performance of fish have primarily focused on adult or large-sized fish species, such as Acipenser sturio, Argyrosomus japonicus, Anguilla japonica, Etelis coruscans, and Myxocyprinus asiaticus [3][4][5][6][7]. In China, numerous stock enhancement programs have been implemented in recent decades, with their scale expanding each year.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of appropriate tagging methods should be based on factors such as fish species, fish size, tagging cost, and characteristics of the study area. Due to its advantages of individual recognition and no need to recapture, acoustic telemetry was widely used in studies about the post-release movement of fishes, such as applications on Acipenser sturio [3], Argyrosomus japonicus [4], Anguilla japonica [5], Etelis coruscans [6], and Myxocyprinus asiaticus [7]. However, the acoustic telemetry was expensive and had large tags, which made it unsuitable for small-sized juvenile fish.…”
Section: Introductionmentioning
confidence: 99%
“…Stocking is used widely as a conservation method for threatened sturgeon species (Carrera‐García, Rochard, & Acolas, ; Welsh & Jackson, ), and it is one of the elements implemented in the restoration of Atlantic sturgeon ( Acipenser oxyrinchus Mitchill, 1815) to the Baltic Sea basin (Gessner et al, ; Kolman, Kapusta, Duda, & Wiszniewski, ). Survival immediately after release can be low and predation is one of the reasons for this (Brown & Laland, ; Olla, Davis, & Ryer, ; Rooker, Holt, & Holt, ).…”
Section: Introductionmentioning
confidence: 99%